Use of Silicone Sizers in Implantation of Porous Polyethylene Nasal Dorsal Implants in Asians - Pham, Randal (Hindawi Publishing Corporation, 2011)
Introduction. A new technique of implantation of high-density porous polyethylene nasal dorsal implants in Asians is described in this paper. Silicone sizers, which have smooth surfaces, were used to facilitate implantation of porous polyethylene implants in Asian patients. Materials and Methods. Twenty-three patients of Asian descent underwent dorsal augmentation rhinoplasty with open technique using high-density porous polyethylene implants. In all cases, silicone sizers were used to facilitate implantations of high-density porous polyethylene nasal dorsal implants. Patient selection criteria exclude patients with history of cocaine use, history of nasal or sinus disorders, previous nasal surgery, deviated septum, poor cartilage support, and thin skin. Results. No bleeding, infection, rejection, displacement, or extrusion was noted. One implant was removed because of a patient's dissatisfaction with the resulting tip height. Conclusion. The use of silicone sizers to facilitate implantations of high-density porous polyethylene nasal dorsal implants was safe and efficacious.